2019
DOI: 10.4314/bcse.v33i2.11
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of sulfonamide-based 1,3,4-oxadiazole derivatives

Abstract: A novel series of 1,3,4-oxadiazole containing sulfonamide derivatives were synthesized by 5-(5cyclohexyl-1,3,4-oxadiazol-2-yl)-2-methyl-benzenesulfonyl chloride. A good yield of intermediate with various substituted like aryl/hetero was formed. All the synthesized compounds were characterized by FT-IR, 1 H NMR, 13 C NMR and mass spectral studies. These compounds were evaluated for their preliminary bioassay in vitro antimicrobial activity, anti-inflammatory and anti-diabetic activities. In this series, most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The chemical hardness (η) is one of the properties of the molecule used to measure the intensity of chemical reactivity. A lower chemical hardness means a less stable and more reactive compound (33). The increasing order in terms of values of η for phenolic compounds is 7 < 5…..< 1 < 8.…”
Section: Dft Studies Resultsmentioning
confidence: 99%
“…The chemical hardness (η) is one of the properties of the molecule used to measure the intensity of chemical reactivity. A lower chemical hardness means a less stable and more reactive compound (33). The increasing order in terms of values of η for phenolic compounds is 7 < 5…..< 1 < 8.…”
Section: Dft Studies Resultsmentioning
confidence: 99%
“…As a result, it is critical to develop and find new antimicrobial medications that are both safer and more effective [3]. According to a review of the literature, 1,3,4-oxadiazole has antifungal [4,5], antimicrobial [6][7][8], antihypertensive [9], anticonvulsant [10], antiviral [11], anti-inflammatory [12], and anticancer activity [13].…”
Section: Introductionmentioning
confidence: 99%
“…This challenges the treatment even though previously used antibiotics or antimicrobial drugs are no longer effective, and infections become progressively difficult to treat. 2 Hence, it is essential to design and discover new and safer as well as more effective antimicrobial drugs, 3 Literature survey revealed that 1, 3, 4-oxadiazole possess diverse pharmacological activities such as anticancer, 4 antimicrobial, 5,6 antihypertensive, 7 anticonvulsant, 8 antimalarial, 9 antiviral, 10 anti-inflammatory. 11 Some of 2, 5-disubstituted 1, 3, 4-oxadiazole based entities have emerged as most potent antimicrobial activities.…”
Section: Introductionmentioning
confidence: 99%